DEVELOPMENT OF FE-CR-MN FUSION MATERIAL COMPOSITION WITH AUSTENITE METASTABILITY REGULATION - Zusin, A. (Collection of scientific papers «ΛΌГOΣ», 2023)
The problem of resource saving is one of the most urgent, because in various industries hundreds of thousands of tons of metal are spent annually to manufacture spare parts and replace parts that wear out quickly. At the same time, replacement of wear parts increases the downtime of equipment and reduces the efficiency of machines and equipment. An effective solution is the repair of machine parts by means of electric arc cladding. In most cases, expensive alloying materials are used for this purpose, which leads to higher cost of parts. This problem can be solved by developing new materials for surface surfacing that provide improved performance characteristics. The aim of the work is to substantiate the chemical and structural composition of the clad metal using economically alloyed Fe-Cr-Mn cladding material with a controlled amount of metastable austenite [1]. The subject of research is the processes of formation of the clad metal during cladding with flux-cored wires under the flux layer. The chemical composition of Record SK flux is given in (Table 1). In order to study the possibility of alloying the clad metal to the required chemical composition, it was decided to perform cladding with PP-Np-14X12Г12СТ flux-cored wire under a layer of Record SK flux with the addition of FeCr and FeMn in different proportions (Table 2).